Comparative inequalities in child dental caries across four countries: Examination of international birth cohorts and implications for oral health policy. - Sharon Goldfeld; Kate L Francis; Elodie O'Connor; Johnny Ludvigsson; Tomas Faresjö; Beatrice Nikiema; Lise Gauvin; Junwen Yang-Huang; Yara Abu Awad; Jennifer J McGrath; Jeremy D Goldhaber-Fiebert; Åshild Faresjo; et al. (PLoS ONE, 2022)
Child dental caries (i.e., cavities) are a major preventable health problem in most high-income countries. The aim of this study was to compare the extent of inequalities in child dental caries across four high-income countries alongside their child oral health policies. Coordinated analyses of data were conducted across four prospective population-based birth cohorts (Australia, n = 4085, born 2004; Québec, Canada, n = 1253, born 1997; Rotterdam, the Netherlands, n = 6690, born 2002; Southeast Sweden, n = 7445, born 1997), which enabled a high degree of harmonization. Risk ratios (adjusted) and slope indexes of inequality were estimated to quantify social gradients in child dental caries according to maternal education and household income. Children in the least advantaged quintile for income were at greater risk of caries, compared to the most advantaged quintile: Australia: AdjRR = 1.18, 95%CI = 1.04-1.34; Québec: AdjRR = 1.69, 95%CI = 1.36-2.10; Rotterdam: AdjRR = 1.67, 95%CI = 1.36-2.04; Southeast Sweden: AdjRR = 1.37, 95%CI = 1.10-1.71). There was a higher risk of caries for children of mothers with the lowest level of education, compared to the highest: Australia: AdjRR = 1.18, 95%CI = 1.01-1.38; Southeast Sweden: AdjRR = 2.31, 95%CI = 1.81-2.96; Rotterdam: AdjRR = 1.98, 95%CI = 1.71-2.30; Québec: AdjRR = 1.16, 95%CI = 0.98-1.37. The extent of inequalities varied in line with jurisdictional policies for provision of child oral health services and preventive public health measures. Clear gradients of social inequalities in child dental caries are evident in high-income countries. Policy related mechanisms may contribute to the differences in the extent of these inequalities. Lesser gradients in settings with combinations of universal dental coverage and/or fluoridation suggest these provisions may ameliorate inequalities through additional benefits for socio-economically disadvantaged groups of children.